Implementasi Penyimpanan Data Sensor Nirkabel dengan MongoDB pada Lingkungan IOT Menggunakan Protokol MQTT - Pramudya Mahardika Kusumawardhana; Mochammad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Internet of Things (IoT) is the machine-to-machine or machine to application communication concept which has the vision that billion of sensors, actuators, and many daily devices could be connected to the internet. Message Queue Telemetry Transport (MQTT) is one of the protocol included in Internet of Things which is useful to save power and reduce the size of packet data messaging. Therefore, it is important to study the ability of modern IoT systems to handle high rates of data updates coming from devices. The upcoming thing in the future is about storage media to handle the IoT data, such as a database system to store the data. A flexible database which could handle the data from the IoT device is required. The writer in this work will evaluated the performance of Not Only SQL (NoSQL) MongoDB Database towards MQTT Protocol. In this work, writer use the parameter for the performance testing is the Load Testing. The process practice for the MQTT Protocol as a sensor data transmission media uses NodeMCU microcontroller with the publish and subscribe method. Load Testing method was choosen as a technique to test the relation between the execution time of MongoDB to store the data of the sensor from MQTT protocol. From this work, claimed that NodeMCU could be configurated with MQTT Protocol, with a 75% accuracy of success for connection within the range from 4 meter to 20 meter. From this work we also got that the execution time for MongoDB to store 50 to 1500 data without the database being configured is less than 0.5 Second, and the execution time for MongoDB to store 50 to 1500 data if the database was already set needs less than 0.2 second to store.